THE IMPACT OF DIGITAL LEARNING LICENSES ON ACCESS TO EDUCATION IN PRIMARY SCHOOLS: A LITERATURE REVIEW - Ramadhani Lubis, Renni; Mariana Parinduri, Wina; Rahmayanti Rambe, Titin; Rambe, Nurhamimah; Fadli, Muhammad (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2024)
This research aims to analyze and identify various previous research results related to the impact of digital learning licenses on access to education in elementary schools. This research is qualitative research using a literature review approach. The data used in this research are scientific articles and journals that are relevant to the research topic. The data sources selected include research published within the last 5 years, which discusses issues related to digital learning licensing, educational access, and technology implementation at the basic education level. The data collection technique used is through academic databases such as Google Scholar, JSTOR, ProQuest, and so on. By using keywords such as "digital learning license", "digital education access", "educational technology in primary schools". The data was analyzed qualitatively with stages of data reduction, data presentation, and drawing conclusions. Based on the research results, it is known that digital learning licenses, both open and paid, have a significant impact on access to education in elementary schools. Open licenses provide broader access and more affordable costs, while paid licenses, although offering more advanced features, often limit access especially in schools with limited budgets. Infrastructure challenges and economic disparities remain major inhibiting factors in harnessing the potential of digital learning technology. Therefore, efforts to increase access to digital education must include investments in infrastructure as well as policies that support the use of open licenses and technology based learning throughout elementary schools.